Le cadre de viabilité de la dette appliqué aux pays à faible revenu - Beddies, Christian H. (International Monetary Fund, 2009)
Low-income countries continue to face significant challenges in meeting their vast development needs while maintaining a sustainable debt position, even after many of these countries have benefited from substantial debt relief. These challenges are further exacerbated by changes in the financial landscape, including the emergence of new creditors and investors, the use of more complex financing vehicles, and the development of domestic markets. The joint World Bank/IMF debt sustainability framework is well placed to help address these challenges and reduce the risks of renewed episodes of debt distress. This paper explains the analytical underpinnings of the framework and the means to ensure its full effectiveness